Customer Satisfaction and Service Quality as Determinants of Customer Loyalty in Nigerian Hospitality Industry - Gawuna, Muhammad Sani; Abdul Rahman, Maria (2017)
It has been established in the literature that there exist consistent justification for the effect of customer satisfaction and service quality on customer loyalty in most service industries.However, substantial numbers of these studies were conducted in advanced countries ranging from the United States of America, Canada, European countries, China, Malaysia, India and other countries outside Africa. Hence, the need to replicate these studies in Africa and Nigeria in particular considering the present economic challenges the country is presently experiencing, which to a large extent have a negative impact on the patronage of goods and services.Specifically, the paper intends to ascertain the attributes capable of generating customer loyalty in the hotels.It also seeks to identify the correlation among customer satisfaction, service quality and hotels guest loyalty in Nigeria. As Shoemaker and Lewis (1999) observed that hospitality industry’s survival lie solely on their ability to achieve customer loyalty.Therefore, the study proposed that a positive and significant relationship exists between; customer satisfaction, service quality and customer loyalty.Therefore, after review of extant literature, the study found that positive and significant relationship exists between the studied variables.It therefore recommends that hotel industry managers should strive and ensure that their offerings are in conformity or even exceed the requirements of their esteemed guests.